Characteristics and Methodology of Education of the Physical Qualities of College Students (Eurasian Journal of Learning and Academic Teaching, 2023)
Pedagogical experiences testify that positive results can be achieved in the development of the basic physical qualities of students even in the conditions of physical education classes twice a week, and the main attention should be paid to the development of the qualities of quickness, quickness, flexibility, agility and general endurance.